Molecular mechanism of PD-1/PD-L1 blockade via anti-PD-L1 antibodies atezolizumab and durvalumab - Hyun Tae Lee (Nature Portfolio, 2017)
Abstract In 2016 and 2017, monoclonal antibodies targeting PD-L1, including atezolizumab, durvalumab, and avelumab, were approved by the FDA for the treatment of multiple advanced cancers. And many other anti-PD-L1 antibodies are under clinical trials. Recently, the crystal structures of PD-L1 in complex with BMS-936559 and avelumab have been determined, revealing details of the antigen-antibody interactions. However, it is still unknown how atezolizumab and durvalumab specifically recognize PD-L1, although this is important for investigating novel binding sites on PD-L1 targeted by other therapeutic antibodies for the design and improvement of anti-PD-L1 agents. Here, we report the crystal structures of PD-L1 in complex with atezolizumab and durvalumab to elucidate the precise epitopes involved and the structural basis for PD-1/PD-L1 blockade by these antibodies. A comprehensive comparison of PD-L1 interactions with anti-PD-L1 antibodies provides a better understanding of the mechanism of PD-L1 blockade as well as new insights into the rational design of improved anti-PD-L1 therapeutics.